2014
DOI: 10.1002/2014jd022326
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal change of diurnal temperature range and its relationship with sunshine duration and precipitation in China

Abstract: We examined the spatiotemporal variation in diurnal temperature range (DTR) and discussed the reasons for the changes of DTR in China based on data from 479 weather stations from 1962 to 2011. Results showed that DTR decreased rapidly (0.291°C/decade) from 1962 to 1989 due to slightly decreased T max and significantly increased T min , but the decrease in DTR has stopped since 1990 as T max and T min kept pace with each other. During 1990-2011, DTR remained trendless, with slight increase in the 1990s and slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 77 publications
14
103
3
Order By: Relevance
“…Rates of change for TM and TN showed similar spatial patterns, with the warming in the southeast region being generally weaker than the warming in the northwest region; however, for TX, severe warming was observed in the southeast. The increase in TN was larger than the increase in TX across the plateau as a whole, which is consistent both with global trends (Braganza, 2004;Lewis and Karoly, 2013) and with other regional trends (Shen et al, 2014;Wang et al, 2014). The inconsistent rates of change between TX and TN result in a general decrease in DTR, which is highly sensitive to small changes in either TX or TN (Dai et al, 1999).…”
Section: Discussionsupporting
confidence: 63%
“…Rates of change for TM and TN showed similar spatial patterns, with the warming in the southeast region being generally weaker than the warming in the northwest region; however, for TX, severe warming was observed in the southeast. The increase in TN was larger than the increase in TX across the plateau as a whole, which is consistent both with global trends (Braganza, 2004;Lewis and Karoly, 2013) and with other regional trends (Shen et al, 2014;Wang et al, 2014). The inconsistent rates of change between TX and TN result in a general decrease in DTR, which is highly sensitive to small changes in either TX or TN (Dai et al, 1999).…”
Section: Discussionsupporting
confidence: 63%
“…() and You et al . (), and it is similar to the results obtained in other regions, such as Northeast China (Shen et al, ) and South America (Vincent et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…And the results showed that in our study watershed the evaporation paradox phenomenon may be caused by sunshine duration decrease, and were similar to a previous study. Sunshine duration is one of the most important meteorological factors, and researchers have found that many regions in china had a decreasing trend in 1961-2000 -similar to the trend in other regions of the earth [37][38]. And in Guangxi Province (the location of the study area), sunshine duration also showed a decreasing trend of -35.1h/10a [39].…”
Section: Relations Between Potential Evapotranspiration and Other Weamentioning
confidence: 99%